Reduction of inflammatory biomarkers underlies extracellular vesicle mediated functional recovery in an aged monkey model of cortical injury - Ryan P. McCann; Bethany Bowley; Monica Pessina; Qiong Yang; Hongqi Xin; Sarah A. DeVries; Mingjin Wang; Yi Zhang; Michael Chopp; Zhenggang Zhang; Douglas L. Rosene; Douglas L. Rosene; et al. (Frontiers in Aging Neuroscience)
Cortical injury results in inflammation and cell death that can cause disability, especially in the aged population. Previous studies from our group have demonstrated the efficacy of bone marrow mesenchymal stromal cell derived extracellular vesicles (MSC-EVs) as a therapeutic to mitigate damage and enhance recovery in our aged monkey model of cortical injury. In the first 3–5 weeks following injury to the hand representation of the primary motor cortex, monkeys treated intravenously with MSC-EVs exhibited a more rapid and complete recovery of fine motor grasp compared to vehicle-treated monkeys. However, whether recovery and treatment are associated with temporal changes in peripheral or central biomarkers of inflammation remain unknown. The current study used the highly sensitive Olink® Proximity Extension Assay to assess inflammatory protein biomarkers in blood and CSF across a 6-week recovery period in aged female monkeys. MSC-EV treatment promoted a sustained downregulation of pro-inflammatory proteins in plasma across the entire recovery period, and a transient downregulation of anti-inflammatory proteins at 2 weeks post-injury. Functional annotation and pathway analyses showed that the plasma proteins downregulated with MSC-EV treatment were associated with the suppression of pro-inflammatory signaling. Further, immunolabeling of perilesional brain tissue harvested 6-weeks post injury showed an increase in homeostatic microglial phenotypes with MSC-EV treatment. Downregulation of inflammatory markers in plasma and brain tissue were positively correlated with improved functional recovery. These data suggest that MSC-EVs facilitate recovery of function after brain injury, in part, via sustained suppression of both peripheral and central pro-inflammatory signaling across recovery.